Patterns of beta-blocker use and dose optimization among ambulatory heart failure patients with reduced ejection fraction (HFrEF) attending public hospitals in Northeast Ethiopia: a multi-center cross-sectional study - Minimize Hassen; Tsehaynesh Kebede Ebsa; Oumer Sada Muhammed; Tewodros Solomon; Mulat Belete Demessie; Teklehaimanot Fentie Wendie; Nuhamin Alemayehu Tesfaye; Mengistie Yirsaw Gobezie (BMC Cardiovascular Disorders)
Abstract Background Evidence-based beta-blockers are essential in managing heart failure with reduced ejection fraction (HFrEF) and are known to improve cardiovascular outcomes. Despite robust nascent guideline recommendations, studies indicate that beta-blockers are often underutilized or administered below target doses. This shivery issue is particularly relevant in Ethiopia, where comprehensive evaluations of beta-blocker utilization and dosing practices are limited. The Northeast region, specifically Dessie, remains underexplored in this context. Objective This study aimed to evaluate the appropriate usage trend and dose optimization of beta-blockers among HFrEF patients attending ambulatory clinics of Dessie Comprehensive Specialized Hospital (DCSH) and Boru Meda General Hospital (BMH), Dessie, Ethiopia, 2024 G.C. Methods A cross-sectional, multi-center study was conducted from February 1 to July 30, 2024, involving 200 randomly selected adult patients with confirmed HFrEF (120 from DCSH and 80 from BMH), who had at least 6-month regular follow-up visits at their respective ambulatory clinics. The study rigorously followed the latest (2022) American Heart Association (AHA) guideline recommendation. Patient’s medical records was reviewed to gather the necessary data. A logistic regression analysis was performed to identify factors associated with beta-blocker use. Statistical significance was declared at p-value < 0.05. Results Among the 200 patients, 88% were prescribed beta-blockers. About 15% of the patients were not receiving beta-blockers whereas they are indicated. Out of the total, 96.5% received guideline-recommended beta-blockers, with bisoprolol being the most common (65%), followed by metoprolol (29%) and carvedilol (3%). Only 13% of beta-blocker users were on optimal doses, with average daily doses of 27.9 mg for metoprolol succinate, 10.0 mg for carvedilol, and 4.8 mg for bisoprolol. Factors positively associated with beta-blocker use included Angiotensin Converting Enzyme Inhibitor use (AOR: 15.48, 95% CI: 2.11-113.54, p = 0.007), and taking multiple medications (AOR: 7.12, 95% CI: 1.54–33.02, p = 0.012), while ingestion of secondary prevention agents (AOR: 0.05, 95% CI: 0.01–0.98, p = 0.048) and male gender (AOR: 0.08, 95% CI: 0.01–0.47, p = 0.005) were negatively associated. Baseline ejection fraction of 25–40% (AOR: 5.44, 95% CI: 1.09–27.12, P = 0.039) was a sole predictor for sub-optimal beta-blocker use. Conclusion Although most patients with HFrEF were prescribed evidence-based beta-blockers, only a limited number reached the optimal dosing levels. It is crucial to align clinical practice with the latest guidelines, prioritize ongoing research, and enhance educational efforts for both healthcare providers and patients. By doing so, it is possible to significantly improve the effective utilization of beta-blockers, ultimately leading to better patient outcomes in this region.